Chitosan-based electrolyte for secondary lithium cells - Arof, Abdul Kariem; Osman, Z.; Morni, N.M.; Kamarulzaman, N.; Ibrahim, Z.A.; Muhamad, M.R. (Springer Verlag (Germany), 2001)
The system chitosan : ethylene carbonate : LiCF3SO3 was prepared by the solution cast technique. To verify that the conductivity of the material is due to the salt, the electrical conductivity at room temperature of the chitosan acetate film and that of the chitosan acetate films containing different amounts of ethylene carbonate added to it were measured. The order of magnitude of the electrical conductivity was 10(-)10 S cm(-)1. Films containing fixed content of chitosan and plasticizer but different amounts of salt were then prepared in the same manner and the highest electrical conductivity obtained was 1.3 x 10(-5) S cm(-)1 at room temperature. These results indicate that the conductivity is due to the salt. Conductivity-temperature studies show that the ln sigma T versus 10(3)/T graphs obey Arrhenius rule implying that the conductivity occurs by way of some thermally assisted mechanism. Polarization current measurement shows that the lithium ion transference number is similar to0.09. A LiMn2O4/chitosan-LiCF3SO3/C cell was fabricated which cycled between 1.5 to 2.5 V with fading capacity. This could be the result of LiF formation due to interaction between the salt and the fluorine in the binding agent. (C) 2001 Kluwer Academic Publishers.